Acute resveratrol supplementation in coronary artery disease: towards patient stratification. (2nd January 2020) - Diaz, M.; Avila, A.; Degens, H.; Coeckelberghs, E.; Vanhees, L.; Cornelissen, V.; Azzawi, M.
Abstract: Objective: Resveratrol (RV) is a polyphenol with antioxidant, anti-inflammatory and cardio-protective properties. Our objective was to investigate whether acute supplementation with high doses of RV would improve flow-mediated dilation (FMD) and oxygen consumption (VO2 ) kinetics in older coronary artery disease (CAD) patients. Design: We employed a placebo-controlled, single-blind, crossover design in which ten participants (aged 66.6 ± 7.8 years) received either RV or placebo (330 mg, 3× day −1 ) during three consecutive days plus additional 330 mg in the morning of the fourth day with a seven-day wash-out period in-between. On the fourth day, FMD of the brachial artery and VO2 on-kinetics were determined. Results: RV improved FMD in patients who had undergone coronary artery bypass grafting (CABG; –1.4 vs . 5.0%; p = .004), but not in those who had undergone percutaneous coronary intervention (PCI; 4.2 vs . –0.2%; NS). Conclusion: Acute high dose supplementation with RV improved FMD in patients after CABG surgery but impaired FMD in patients who underwent PCI. The revascularization method-related differential effects of RV may be due to its direct effects on endothelial-dependent dilator responses. Our findings have important implications for personalized treatment and stratification of older CAD patients.